A STUDY OF SOCIOLOGY: THE PORTRAYAL OF WOMEN IN PATRIARCHAL SOCIETY IN ROMEO AND JULIET BY SHAKESPEARE AND DATU MUSENG AND MAIPA DEAPATI BY FAHMI SYARIF - Jusrani, Jusrani; Junaid, Syahruni (Study Program of English Literature, 2021)
Abstract. This paper talks about the women’s character formed in the society of patriarchy system portrayed in the play of Romeo and Juliet,represented the England culturedepiction in the middle of 14th century and in the play of DatuMuseng and Maipa Deapati, represented the Bugis Culture Depiction of South Sulawesi in the end of 18th century. The aim of this paper is to describe the image of women in the eyes of society of two different places and different countries represented in the two differentplays. The writer used the analytical approach of the sociology study by using theory of Allan G Johnson and designed this paper as a descriptive qualitative method by collected data from several articles that related to the topic. The result shows thatin the patriarchy system, men were given privilege by the society, while the women just seen as a lowest class in the society. According to Allan G Johnson, there are four elements of patriarchy system: Male dominance, Male Identification, Male centeredness, and Male obsession with control. From this elements, we can see the position of women, where women must follow the father’s rule, women must marry with her father’s choice, and women don’t have any right to take decision. Keywords: Women, Society, Romeo and Juliet, DatuMuseng and MaipaDeapati, Patriarchy System Culture